2003
DOI: 10.1111/j.1749-6632.2003.tb07371.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Trematode Cercariae Carrying Neorickettsia risticii in Freshwater Stream Snails

Abstract: We provide evidence of Neorickettsia (Ehrlichia) risticii Holland, the agent of Potomac horse fever, in trematode larval stages found in aquatic snails and insects collected from a stream in Korea, using nested polymerase chain reaction (PCR) and sequence analysis of the 16S rRNA gene fragment amplified from several cercaria species. It was observed that of 423 (13.1%) of 3,219 snails infected with cercariae, 77 (20.8% of the 371) were infected with N. risticii. Five families of trematode cercariae, Schistosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…However, as a result of combined molecular and experimental approaches it was demonstrated to be associated with digeneans [14-18]. Since then, N. risticii was detected in representatives of several digenean families, e. g., Lecithodendriidae, Plagiorchiidae, Microphallidae, Macroderoididae, and Echinostomatidae [7,17-25]. Although the digenean hosts of N. risticii have diverse life cycles that utilize various groups of invertebrates and even vertebrate intermediate hosts, it has been shown that amphibiotic insects such as mayflies and caddisflies play a particularly important role in the epizootology of Potomac horse fever [20,22,26].…”
Section: Introductionmentioning
confidence: 99%
“…However, as a result of combined molecular and experimental approaches it was demonstrated to be associated with digeneans [14-18]. Since then, N. risticii was detected in representatives of several digenean families, e. g., Lecithodendriidae, Plagiorchiidae, Microphallidae, Macroderoididae, and Echinostomatidae [7,17-25]. Although the digenean hosts of N. risticii have diverse life cycles that utilize various groups of invertebrates and even vertebrate intermediate hosts, it has been shown that amphibiotic insects such as mayflies and caddisflies play a particularly important role in the epizootology of Potomac horse fever [20,22,26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on E. coelmaticum and E. pancreaticum were greatly focused on their morphology, life history, main organs and their functions, and epidemic investigation (Vykhrestyuk and Yarygina 1982;Pinheiro and Amato 1995;Dorny et al 1996. However, no molecular data on E. coelmaticum and E. pancreaticum are available at present, and their relationship is not determined based on molecular data, which have successfully been used in the analysis of phylogeny and in the identification of trematodes (Attwood et al 2002;Park et al 2003;Olson et al 2003). Until recently, only three partial 18S rRNA sequences of three genera, Brachylecithum, Lyperosomum, and Dicrocoelium, are available and two of them have been used in molecular phylogenetic analyses (Olson et al 2003).…”
mentioning
confidence: 99%
“…of trematodes, and Myotis yumanensis bats and tree swallows (Hirundo rustica and Tachycineta bicolor) were also reported to be infected with N. risticii (10). In addition, N. risticii DNA fragments have been detected in various other digenean trematodes having life cycles typical of freshwater/terrestrial ecosystems (11,12). However, due to limited molecular analysis, the relatedness of these Neorickettsia organisms to N. risticii strains infecting horses, and whether they can infect horses and cause PHF, is unknown.…”
mentioning
confidence: 91%